Digital innovations and smart solutions for society and economy: Pros and cons - Marcin Sikorski (Foundations of Management, 2021)
Recent developments in artificial intelligence (AI) may involve significant potential threats to personal data privacy, national security, and social and economic stability. AI-based solutions are often promoted as "intelligent" or "smart" because they are autonomous in optimizing various processes. Because they can modify their behavior without human supervision by analyzing data from the environment, AI-based systems may be more prone to malfunctions and malicious activities than conventional software systems. Moreover, due to existing regulatory gaps, development and operation of AI-based products are not yet subject to adequate risk management and administrative supervision. Resonating to recent reports about potential threats resulting from AI-based systems, this paper presents an outline of a prospective risk assessment for adaptive and autonomous products. This research resulted in extensive catalogs of possible damages, initiating events, and preventive policies that can be useful for risk managers involved in conducting risk assessment procedures for AI-based systems. The paper concludes with the analysis and discussion of changes in business, legal, and institutional environments required to ensure the public that AI-based solutions can be trusted, are transparent and safe, and can improve the quality of life.
Keywords: M10; 650; digital innovations; digital services; artificial intelligence; smart services; risk assessment; risk management